Patient-Reported Outcome Measurement Information System (PROMIS) Scores in Pediatric Idiopathic Toe Walkers. Issue 8 (29th September 2022) - Lindsay, Sarah E.; Bauer, Jeremy; Bouton, Daniel; Do, Patrick; Woodmark, Carly; Sienko, Susan; Raney, Ellen M.
Abstract : Background: Idiopathic toe walking (ITW) can result in early contact with the health care system and be distressing for patients and their families. The natural history of ITW is poorly characterized. Deciding how and when to intervene can be difficult. Patient-reported outcomes are utilized in the clinical setting to assess patient factors and indications that may better inform treatment plans. Patient-Reported Outcomes Measurement Information System (PROMIS) is an instrument designed to collect patient-reported outcomes. Minimum clinically important differences in PROMIS metrics have been established to facilitate clinical relevance and utility of these metrics. The purpose of this study was to characterize the patient perspective of ITW by utilizing the PROMIS scores. Methods: Retrospective chart review was performed to identify children aged 5 to 17 with a diagnosis of ITW treated at a single tertiary care center between 2017 and 2020. Inclusion criteria were a diagnosis of ITW and completion of a PROMIS questionnaire. Exclusion criteria were neurologic disease, autism, and previous surgical treatment. Demographic, physical exam, treatment, and available motion analysis data were collected. PROMIS scores for the following domains were available: Mobility, Peer Relationships, and Pain Interference. Results: Forty-five children were enrolled. Seventy-three percent of PROMIS scores were patient reported while the remainder were parent reported. PROMIS score means for the cohort by domain were Mobility: 45.2±8.2 ( P <0.000); Peer Relationships: 46.4±11.6 ( P =0.047); and Pain Interference: 47.4±9.5 ( P =0.67). Motion analysis data, available for 11 children, noted age-matched gait velocity negatively correlated ( r s =−0.652, P =0.03) with Peer Relationships. No correlations were found between other aspects of gait, body mass index, or limitations in dorsiflexion and PROMIS domains. Parents reported lower Mobility scores than children did. There were no other significant differences between patient-reported and parent-reported PROMIS scores. PROMIS scores did not differ significantly between those <10 years and those ≥10 years. Conclusion: In this cohort of 45 otherwise healthy children without other neurologic diagnoses, there are both clinically and statistically significant differences in PROMIS means between our cohort and the healthy age-matched population. These differences manifested in worse peer relationships and mobility scores. Level of Evidence: Level IV.